A Study on the Application of Different Types of Mulches on Some Growth Characteristics of Two Varieties of Tagetes in Mashhad Urban Vegetation - P. Pakdel; A. Tehranifar; S. H. Nemati; A. Lakzian; S. M. Kharrazi (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2015)
In this study, the effects of four types of mulch including wood chips, municipal compost, sawdust and gravel in three different thicknesses on temperature soil, moisture and growth characteristics of two cultivars of Tagetes (Tagetes patella var Durango Bee and Tagetes erecta var Antigua) were examined in Mashhad area with semi-arid climate. The research was conducted as a split plot based on a completely random block design with four replications. Treatments included control (no mulching) and four types of mulch including wood chips, municipal compost, sawdust and gravel in three thickness levels (4, 8 and 12 cm). During the study, soil moisture and temperature, total flower number, fresh and dry weight of plant, plant height and fresh weight of root were measured. Sawdust mulch with 12 cm thickness had the highest soil moisture (23.62%) and lowest soil temperature (25.01ºC), and led to greater increases in growth characteristics of the two cultivars. In both cultivars, increasing of mulch thickness led to the increased rate of growth. The Antigua cultivar showed a better vegetative growth, smaller flower number, and larger flowers in comparison with Durango Bee cultivar. All mulch types were significantly different from control. Overall, in both cultivars the highest and smallest growth taits were detected in sawdust and control, respectively. It seems that sawdust by preserving soil moisture and reducing drought stress out performs the other mulches in dry and semi-arid areas.